Silent magnetic resonance angiography diagnostic value of intracranial unruptured aneurysms - Bin Lv; Tingyang Zhang; Ning Wang; Lu Liu; Mingyu Li; Meng Li; Mingguang Sun; Xiao Zang; Xinfeng Liu; Rongju Zhang; Xiangyu Cao; Zhihua Du; et al. (Scientific Reports)
Abstract Silent magnetic resonance angiography (S-MRA) is primarily utilized to assess the blood flow in aneurysms and parent vessels of treated intracranial aneurysms. This study aimed to compare the diagnostic value of S-MRA and three-dimensional time of flight (3D-TOF) MRA for unruptured intracranial aneurysms. We included patients diagnosed with unruptured intracranial aneurysms using digital subtraction angiography (DSA) who subsequently underwent S-MRA and 3D-TOF MRA. Two independent neuroimaging and neurointerventional doctors evaluated the DSA images and measured aneurysm dimensions. Using DSA results as the gold standard, we determined the sensitivity and specificity of S-MRA and 3D-TOF MRA, as well as their accuracy in measuring aneurysm size and identifying aneurysms with daughter sacs. We detected a total of 41 intracranial aneurysms (in 37 patients) on both S-MRA and 3D-TOF MRA, with both techniques achieving a sensitivity and specificity of 100%. For aneurysm height, the intraclass correlation coefficient (ICC) was 0.977 (P < 0.001) between S-MRA and DSA, and 0.908 (P < 0.001) between 3D-TOF MRA and DSA. For neck width, the ICC was 0.663 (P < 0.001) between S-MRA and DSA, and 0.563 (P < 0.001) between 3D-TOF MRA and DSA. In terms of daughter aneurysm detection, 3D-TOF MRA Sensitivity 40%; specificity 92%: positive predictive value 100%; S-MRA sensitivity 60%; specificity 89%; positive predictive value 42%. In conclusion, S-MRA and 3D-TOF MRA did not significantly differ in aneurysm detection ability. For the detection of aneurysm with dauthger sacs indicators, the sensitivity is also higher.